2017
DOI: 10.4274/mirt.30306
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Minimum Apparent Diffusion Coefficient and Maximum Standardized Uptake Value of the Primary Tumor with Clinicopathologic Characteristics in Endometrial Cancer

Abstract: Objective:To explore the correlation of the primary tumor’s maximum standardized uptake value (SUVmax) and minimum apparent diffusion coefficient (ADCmin) with clinicopathologic features, and to determine their predictive power in endometrial cancer (EC).Methods:A total of 45 patients who had undergone staging surgery after a preoperative evaluation with 18F-fluorodeoxyglucose (FDG) positron emission tomography/computerized tomography (PET/CT) and diffusion-weighted magnetic resonance imaging (DW-MRI) were inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…In endometrial cancer, several studies have demonstrated that DWI is useful for evaluating the association between the apparent diffusion coefficient (ADC) of the tumor and the disease extent . Furthermore, an inverse relationship between tumor ADC and pathologic grade has been consistently reported . Of variable tumor ADC values, the minimum value on histogram analysis has been recently investigated in many studies and revealed promising results in associations with pathologic grade .…”
mentioning
confidence: 99%
“…In endometrial cancer, several studies have demonstrated that DWI is useful for evaluating the association between the apparent diffusion coefficient (ADC) of the tumor and the disease extent . Furthermore, an inverse relationship between tumor ADC and pathologic grade has been consistently reported . Of variable tumor ADC values, the minimum value on histogram analysis has been recently investigated in many studies and revealed promising results in associations with pathologic grade .…”
mentioning
confidence: 99%